1977
DOI: 10.1007/bf01250280
|View full text |Cite
|
Sign up to set email alerts
|

The pineal gland of nocturnal mammals I. The pinealocytes of the bat (Nyctalus noctula, Schreber)

Abstract: The ultrastructure of the pinealocytes of noctule bats, mammals which live most of the time in darkness or very low light intensities, was examined and compared with the pinealocytes of other mammals. Two different populations of pinealocytes (I and II) were observed. They differ in general aspect, in location and especially in their content of cell organelles involved in synthetic processes. Mitochondria, ribosomes, lysosomes and lipid inclusions were present in the perikaryon of pinealocytes of both populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

1977
1977
1994
1994

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 35 publications
1
14
0
2
Order By: Relevance
“…It is to be regretted that these authors did not mention the presence or the absence of granular vesicles in these cells. Thus it has not been possible to classify them strictly (see Table 1) as Reiter, 1975) and in po&et gopher (Sheridan and Reiter, 1973) (Pevet et al, 1977) granular pigment has also been described. In this animal, the pinealocytes of population !I are, moreover, characterized by the presence of an extraordinary amount of glycogen granules.…”
Section: Second Category Of Cellsmentioning
confidence: 92%
“…It is to be regretted that these authors did not mention the presence or the absence of granular vesicles in these cells. Thus it has not been possible to classify them strictly (see Table 1) as Reiter, 1975) and in po&et gopher (Sheridan and Reiter, 1973) (Pevet et al, 1977) granular pigment has also been described. In this animal, the pinealocytes of population !I are, moreover, characterized by the presence of an extraordinary amount of glycogen granules.…”
Section: Second Category Of Cellsmentioning
confidence: 92%
“…The occurrence of melanin in the pineal stroma of man (Hiilsemann, 1971;Moller, 19741, baboon (Theron et al, 1987), horse and other equids (Cozzi, 1986;Cozzi and Ferrandi, 1984a,b), rodents (Sheridan and Reiter, 1973;Matsushima and Reiter, 1975), cats (Calvo et al, 1992), and other domestic animals (Santamarina and Meyer-Arendt, 1956;Santamarina, 1958;Bargmann, 1943;Quay, 1974;Vollrath, 1981) however, remains a n engima. Detailed reports on pineal melanin are lacking in bats, which comprise a very large group of approximately 900 species (Honacki et al, 1982;Koopman, 1984 type of pigment, has been reported to be present in the pineal of many mammals, including the vampire bat, Desmodus (Bhatnagar, 19881, and two other bat species (Nyctalus noctula: Pevet et al, 1977; Vesperugo savi: Romita and Gatti, 1980). Among bats, a third type of pigment, hemosiderin, has been reported in the pineal siderotic macrophages of the vampire (Bhatnagar, 1988).…”
mentioning
confidence: 96%
“…The presence of sensory cilia in light and dark pinealo cytes in the Rousettus suggests that these cells may be of a neurosensory origin, as has been proposed for the type I pinealocyte in the hibernating bats, the pipistrelle (Pevet and Racey, 1981] and the noctule [Pevet et al" 1977], In harmony with this interpretation, the club-shaped ciliary terminals appear similar to the outer segment of the rudimentary photoreceptor cell of nonmammalian ver tebrates [Oksche. 1971], A further difference between the pineal of the nonhibernating Rousettus and that of hibernating bats during their reproductive season [Pevet et al, 1977: Pevet andRacey.…”
Section: Discussionmentioning
confidence: 63%
“…1978) and the Malaysian rat [Pevet and Yadav. 1980], In contrast, two structurally dif ferent types of pinealocytes have been described in the Microchiroptera [Pevet et al. 1977: Pevet andRacey, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation